Dual-channel physical random bits generation by a master-slave vertical-cavity surface-emitting lasers chaotic system. (25th September 2018) - Ran, Can; Tang, Xi; Wu, Zheng-Mao; Xia, Guang-Qiong
Abstract: Taking the chaotic output from a master-slave framework chaotic system as chaotic entropy resource, we propose a scheme for acquiring dual-channel high-speed physical random bits (PRBs). For such a scheme, a vertical-cavity surface-emitting laser (VCSEL) under polarization-preserved optical feedback from a fiber Bragg grating is utilized as the master VCSEL ( M -VCSEL). Under suitable operating parameters, both X and Y polarization components ( X -PC and Y -PC) of the M -VCSEL can output chaotic signals with comparable power and weak time-delay signatures. The chaotic outputs from the X -PC and Y -PC of the M -VCSEL are divided into two parts, and then injected into the corresponding polarized component of another VCSEL (named as slave VCSEL, S -VCSEL) after undergoing different flight-time, and such an injection method is named as dual-path polarization-preserved optical injection (DP-PPOI). The X -PC and Y -PC in the S -VCSEL under DP-PPOI can simultaneously output chaotic signals with enhanced bandwidth, which are quantified by 8-bit analog-to-digital converters and taken as the entropy sources for generating dual-channel bit sequence after adopting m least significant bits (m-LSBs) extraction and logical exclusive-OR post-processing. Finally, the randomness of the bit sequences generated under optimized parameters is tested by NIST SP 800-22 statistical test suite. The results demonstrate that dual-channel random bits at rate of 500 Gbit s −1 can be obtained, and the rate of random bits can be further increased to 1 Tbit s −1 through adopting cross-merging method.